Absorption of lithium in montmorillonite: A density functional theory (DFT) study - Wungu, Triati Dewi Kencana (Animo Repository, 2011)
The absorption of lithium in montmorillonite [LiSi8(Al 3Mg)O20(OH)4] was investigated using Density Functional Theory (DFT). The final position of lithium after absorption was found to be in good agreement with an experimental observation where lithium atom migrated from the interlayer into the vacant octahedral site of montmorillonite. The lithium absorbed on montmorillonite was held together by a very strong attraction between ions and exhibited an insulating behavior as depicted from the density of states curve. Due to the presence of lithium in the octahedral site of montmorillonite, the OH group reoriented itself perpendicular to the ab plane and an electron of lithium was transferred in order to compensate the existing net charge of montmorillonite caused by isomorphous substitutions. Relative small charge transfer was observed between lithium and montmorillonite. Copyright © 2011 American Scientific Publishers.